Building library 3.0 : Issues in creating a culture of participation - Evans, Woody; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2009)
Written for information professionals and librarians trying to implement and manage Web 2.0 in their physical and online collections, Building Library 3.0 pays careful attention to the implementation of social web applications, mobile computing, and RFID and QR Code technology. The book details both how to make these technologies work for libraries and also explores why libraries must gain ground in the important new territories of Web 2.0. The changing relationships between information seekers, the information being sought, and the professional information gatekeepers is of great importance in this change, and this book explains both the use of the technology to reach information seeking communities, and the profound ways in which such relationships will change the nature of librarianship.
Part one. Basics -- 1. Library 2.0: the fundamentals -- 2. New library users -- Part two. The people's web -- 3. Folksonomic exchanges: authority of the people -- 4. Social networking: making it work -- 5. Mobile life and QR Code -- 6. Second Life and other massively multi-user environments -- 7. Arphids: promise and dangers -- Part three. Quality and mettle -- 8. Fundamentally good service -- Conclusion: no more walls -- Appendices -- 1. The interviews -- 2. Tips, tricks, and hacks: some ideas -- References -- Index.
Includes bibliographical references and index.
Elsevier
Keywords: Libraries -- Effect of technological innovations on; Library administration; Communication in library science -- Technological innovations; Libraries -- Service learning; Digital libraries; Internet in library reference services; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Communication in library science -- Technological innovations; Digital libraries; Internet in library reference services; Library administration; Electronic books